Clinical Profile and Treatment Outcome of Spinal Epidural Arachnoid Cysts: A Systematic Review of Case Studies and Reports - Aditya K. Patil; Srikant K. Swain; Suresh Sharma; Rajnish Kumar Arora; Achal Sharma; Poonam Arora; Radhey S. Mittal (Indian Journal of Neurosurgery)
Background A spinal epidural arachnoid cyst (SEAC) is a rare clinical entity. We performed a systematic review of the literature to obtain information regarding demographics, clinical presentation, treatment modalities, and outcome of SEACs. Methods A literature search was performed by using the databases PubMed/Medline, PubMed Central, Embase, Cochrane Library, Ovid MEDLINE, and Ovid Medline In-Process. A total of 170 articles were found on literature search. We found 575 cases of SEAC since 1904 for inclusion in the review including three cases which were operated by us. We studied the patient characteristics, clinical features, and management strategies, and evaluated their outcome. Results The average age of presentation was 30 years with a male:female ratio of 1.03:1. They are commonly seen in the thoracic region (42.3%). The length of cyst was more than two vertebral levels in 85.81%. Mean symptom duration was 29 months, with most common presentation being that of compressive myelopathy. A good clinical outcome was present in symptomatic patients who had a shorter symptom duration and underwent complete surgical excision of the SEAC. Age, sex, length of lesion, and presence of dural defect did not have a bearing on the surgical outcome. Conclusion For thoracic compressive myelopathy in a young patient, SEAC should be kept as a differential diagnosis. Surgical complete excision of the cyst with meticulous closure of the dural defect is the standard in management for a good clinical outcome.